2015
DOI: 10.1089/jmf.2014.0021
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Health Effects of Chios Gum Mastic and Peroxisome Proliferator-Activated Receptors: Indications of Common Mechanisms

Abstract: For thousands of years, Chios Gum Mastic (CGM), the resin produced by the trunk of Pistachia lentiscus var Chia, has been used for culinary and medicinal purposes and several therapeutic properties have been attributed to it. CGM has been used in traditional medicine of various nations in the eastern Mediterranean area. This survey was carried out to identify biological mechanisms that could explain traditional usage and recent pharmacological findings. We reviewed the related scientific literature available f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 75 publications
1
16
0
3
Order By: Relevance
“…This supports the idea that the overall effect of CMG on lipid metabolism is mediated via its function as a PPARa agonist. Furthermore, the activation of PPARb/d improves the serum lipid profile, which seems to support the notion that CMG exerts beneficial effects on lipid metabolism [16].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This supports the idea that the overall effect of CMG on lipid metabolism is mediated via its function as a PPARa agonist. Furthermore, the activation of PPARb/d improves the serum lipid profile, which seems to support the notion that CMG exerts beneficial effects on lipid metabolism [16].…”
Section: Resultssupporting
confidence: 76%
“…Trace components include verbenone, a-terpinolene, and linalool-which contribute to the mastic oil's antibacterial activity-and camphene, which has fat-reducing activity [15]. Georgiadis et al [16] remarked that CMG's antibacterial, fat-reducing, and anti-inflammatory activities suggest synergistic effects: ''a combination of several compounds is more potent than any single compound on its own. ''…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the components of SOAE in combination counteracted against LPS-induced inflammation in monocyte-derived macrophages 52 . Considering the fact that the lipophilic molecules of SO, such as lignans, α–tocopherol and phytosterols, have less feasibility to separate out into water (confirmed by the absence of these in SOAE by LC-MS analysis), our published studies 17 , 18 suggest that apart from these lipophilic molecules, SO has other biologically active polar molecules that can counteract inflammation and atherosclerosis. However, the study should in no way be interpreted to suggest that ALL the inflammatory components reside in the aqueous extract.…”
Section: Discussionmentioning
confidence: 82%
“…This finding led us to evaluate whether non-saponifiable components of edible oil that have been overlooked could have properties that would act in synergy with fatty acid components to not only inhibit atherosclerotic properties, but also promote regression. Subsequently, we demonstrated that an aqueous extract (SOAE) from SO was effective in inhibiting inflammation, both in vitro and in vivo 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This superoxide production is inhibited by mastic gum. It is suggested by recent stud-ies that CMG acts as a peroxisome proliferator-activated receptor (PPAR) modulator [45]. PPARs are nuclear receptors that control cellular functions via transcription at the level of gene expression implicated in the pathways of metabolic syndrome, inflammation, atheromatosis, and cancer [36,45].…”
Section: Discussionmentioning
confidence: 99%